2011
DOI: 10.1111/j.1937-5956.2010.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Liability and Patch Release on Software Security: The Monopoly Case

Abstract: An abundance of flawed software has been identified as the main cause of the poor security of computer networks because major viruses and worms exploit the vulnerabilities of such software. As an incentive mechanism for software security quality improvement, software liability has been intensely discussed among both academics and practitioners for a long time. An alternative approach to managing software security is patch release, which has been widely adopted in practice. In this paper, we examine these two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Other refinements for software liability have been suggested [5,2,3,23,4]. These works suggest various types of liability, applied to various parties within the software deployment/development chain.…”
Section: Software Liabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Other refinements for software liability have been suggested [5,2,3,23,4]. These works suggest various types of liability, applied to various parties within the software deployment/development chain.…”
Section: Software Liabilitymentioning
confidence: 98%
“…A European Union working group further suggested that software vendors have upper and lower limited liability thresholds based on the potential harm or criticality of software [4]. Models for liability have examined the effectiveness of different liability policies, finding that their effectiveness can be highly variable depending on the probability of zero-day exploits, the cost of patch deployment, the nature of loss, and whether a software vendor holds a monopoly [3,23].…”
Section: Software Industrymentioning
confidence: 99%
“…Our setting, where the MSSP's protection effort is related to security breach probability, and the fact that the MSSP is liable for the client's damage when protection fails, is commonly seen in the product failure and insurance literature (e.g., [46, Downloaded by [University of Otago] at 06:09 24 July 2015 51,52]). Also, the use of software or system liability as an incentive mechanism in managing security risks has been widely proposed (e.g., [4,31,47]). For example, August and Tunca [6] analyze the impact of different liability policies on software vulnerability and derive the conditions under which loss liability and patch liability can be effective.…”
Section: Related Literaturementioning
confidence: 99%
“…Risk , defined as “uncertainty inherent in doing business” (Straub & Welke, , p. 442), is further divided into business risks of “systems for delivering goods/services to a customer” or systems risk , defined as “the likelihood that the firm's information systems are insufficiently protected against certain kinds of damage or loss” (Straub & Welke, , p. 441–442). The wide application of technology to create business processes blurs these risk categories; business risks are now often systems risks (O'Donnell, ; Ransbotham & Mitra, ; Kim, Chen, & Mukhopadhyay, ). Outside of natural disasters and innate process failures, these risks arise from abuse of vulnerabilities via three enterprise conduits: organizational environment, internal enterprise systems, and the knowledge of individual actors about enterprise systems and their embedded risks (Straub & Welke, ).…”
Section: Introductionmentioning
confidence: 99%
“…ERM strives to catalog a firm's risks, aggregate similar risks, identify correlated risks, and carefully estimate their potential costs to an organization, as inputs to monitor and optimize a firm's actions across a risk portfolio (Nocco & Stulz, ; Wu & Olson, ). Doing so can lessen a firm's exposure to operational risks that can be managed by patching technologies and processes (Nocco & Stulz, ), versus by vendor contract liability clauses (Kim et al., ; August & Tunca, ), insurance, markets, or financial hedging (Anderson & Moore, ; Nocco & Stulz, ). The objective is to generate decision models managers can use to manage risks systematically (Wu & Olson, ), limiting harmful events by internally managing risks for which they have a comparative managerial advantage (Nocco & Stulz, ).…”
Section: Introductionmentioning
confidence: 99%